2000
DOI: 10.1034/j.1399-0039.2000.550302.x
|View full text |Cite
|
Sign up to set email alerts
|

Both the HLA‐DPB1 and ‐DRB1 alleles correlate with risk for multiple sclerosis in Japanese: clinical phenotypes and gender as important factors

Abstract: The purpose of this study was to clarify the association of HLA-DRB1 and -DPB1 alleles with multiple sclerosis (MS) in Japanese, to determine whether optico-spinal MS (OS-MS) and conventional MS are immunogenetically distinct, and to verify the role of gender difference in HLA associations of MS. We studied HLA-DRB1 and -DPB1 polymorphisms in 166 Japanese patients with MS. Forty-seven patients were classified as having the optico-spinal MS (OS-MS) and 119 as having conventional MS. A lack of DPB1*0301 and a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 27 publications
4
52
2
Order By: Relevance
“…[26][27][28][29][30] These observations suggest that the DP molecule could act as a transplantation antigen.…”
Section: Discussionmentioning
confidence: 89%
“…[26][27][28][29][30] These observations suggest that the DP molecule could act as a transplantation antigen.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, the key to observing sex differences among cytokines that distinguish between Th1 responses and Th2 responses in MS is the use of myelin-specific antigens. It is important to note that several studies have reported an association between HLA DR2 (DRB1*1502 and *0501) and female gender in MS (Al-Shammri et al, 2004;Duquette et al, 1992;Fukazawa et al, 2000;Van et al, 1986), highlighting the importance of studying male and female patients separately. We were not trying to repeat these studies, but rather to assess whether our genderskewed cytokine responses can be explained by a disproportionate representation of HLA alleles in our MS patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…First, the density of antigen expression in different target (CNS) areas, in conjunction with the antigen specificity of CNS-autoreactive T cells, has been suggested to influence lesion topography (3)(4)(5). However, in light of the particular animal model used in our study, we can exclude variations of antigen density or T-cell antigen specificity contributing to the observed changes in lesion topography.…”
Section: Discussionmentioning
confidence: 90%
“…The reasons underlying distinct lesion development at different anatomical sites still remain however largely elusive: Some authors have proposed that the nature and expression pattern of the target autoantigen might play a role (3,4). Others have observed an influence of the HLA complex and its role in shaping antigen presentation, thus suggesting that T-cell antigen specificity might impact the location of inflammation (5). Additionally, T-cell polarization into distinct T helper subtypes, as well as their expression pattern of chemokine receptors and adhesion molecules, has been implicated in determining the localization of inflammatory lesions within the CNS (6-8).…”
mentioning
confidence: 99%